"The Universal Andalusian," "The Zealous Andalusian," and the "Andalusian Elegy." - Richard A. Cardwell (Studies in 20th & 21st Century Literature, 1983)
Biographers and critics have been content to repeat Juan Ramón Jiménez' own comments concerning the influence upon him of Krausism, the Institución Libre de Enseñanza and the personality and model of Francisco Giner de los Ríos. In general, little discussion of the nature of that contact and virtually no evidence for arguing the importance or the shape of Krausist ethos on Jiménez' intellectual formation have been adduced. In previous studies I have considered Jiménez' literary apprenticeship in the light of the Krausist contacts. In the present study I further contend that Platero у уо, arguably his best known work, represents not only a major statement of the poet's idealism but that it was written under the spell of Giner's example and teachings. Platero is not only a story for children, it was intended also as an example of Giner's "pedagogía íntima." As such the work can take its place in the main corpus of the poet's work as yet another statement of la ética estética. This essay further clarifies the formative ideological influence of Giner's idealism.
Keywords: Juan Ramón Jiménez; Krausism; Institución Libre de Enseñanza; Francisco Giner de los Ríos; philosophy; nature; Krausist ethos; intellectualism; Platero y yo; la ética estética; ideology; idealism